Penerapan Sistem Informasi Manajemen Puskesmas (Simpus) GizKIA Berbasis Komputer Di Puskesmas Karangdowo Klaten - Valentina, Widyaningrum Kiky, Sri Sugiarsi, SKM, M.Kes, Sri Darnoto, SKM., MPH (2016)
Nutrition SIMPUS KIA (SIMPUS GizKIA) is one application module is intended to help manage the data of pregnant women and babies / toddlers so that the data obtained are valid and accurate. One of the constraints on the management of input data that have been saved can not be edited again thus increasing the workload of midwives. The purpose of this study to determine the Primary Health Care management information system (SIMPUS) GizKIA-based computer in the Primary Health Care Karangdowo Klaten. This type of research is qualitative descriptive study. The population in this study were 20 people from health professionals. The informants are 4 midwives and 4 informants as triangulation using purposive sampling technique. The data in this study is qualitative data in the form of direct interviews with informants. The results of research that flow from the data collection activities of midwives are recorded in advance in the cohort and also PWS KIA, then input by midwives using laptops equipped with offline applications SIMPUS GizKIA. Midwives coordination recapitulate data maternal and child health from 19 villages. Reports are sent to the District Health Office is the recapitulation of maternal and child health. The obstacles are there at the time of data entry, data processing and reporting of data.